Стандарти діяльності прокурора у кримінальному процесі США - Луцик, Василь Васильович (Київський національний університет імені Тараса Шевченка, 2016)
У статті проаналізовано стандарти діяльності прокурора у кримінальному процесі США. Виокремлено види стандартів, їх нормативне регулювання, особливості використання. Зроблено висновок, що Стандарти прокурорської діяльності у кримінальному провадженні США становлять собою уніфіковану систему норм-регуляторів, за допомогою яких сторона обвинувачення може ефективно і раціонально виконувати свої обов’язки, а сторона захисту ‒ контролювати правомірність діяльності прокурора та обґрунтовано оскаржувати дії і рішення прокурора, якщо останні не відповідають стандартам.

The standards of the prosecutor’s activity in the criminal process of the USA regulate criminal procedure prosecutor’s activity at all level in detail. The task of the prosecutor after the receiving a criminal case from the police is solving two issues. Firstly, if there are reasonable grounds to consider that the suspect has committed a crime and whether the evidence is sufficient to accuse somebody. Secondly, the prosecutor must establish whether there is a public interest in the prosecuting of the suspect. The standards of the prosecutor’s activity in criminal process of the USA are analysed in the article. The types of standards, their normative regulation and peculiarities of application are severed. Its concluded that the standards of the prosecutor’s activity in criminal process of the USA constitutes unified system of regulatory norms, using which the accusatory party fulfill its duties effective and rationally, and the defendant party can control the legality of the prosecutor activity and reasonably appeal against the actions and decisions of the prosecutor if the latter did not meet the standards. The introduction of standards of the prosecutor’s activity in criminal process of Ukraine is an urgent need in present conditions, which is caused by expectations of civil society concerning effective functioning of a new independent prosecutor’s office. The existence of standards as instruments of control and influence on the prosecutor from the defense and the victim will lead to the increase of prosecutor’s work level, as well as to the increase of public confidence in the prosecutor’s office, which is extremely actual today.
Keywords: прокурор; стандарти діяльності прокурора; керівні принципи; модельні стандарти; prosecutor; standards of prosecutor’s activity; guidelines; model standards